Satisfied or not? Exploring the interplay of individual, country and international organization characteristics for negotiation success - Diana Panke; Gurur Polat; Franziska Hohlstein (The Review of International Organizations, 2020)
International norms and rules are created in international negotiations. A comprehensive survey shows that the satisfaction with negotiation outcomes varies between delegates, states and International Organizations (IOs), which is important as it has potential ramifications for state compliance and the effectiveness of the international rules and norms. This paper investigates which role individual, country and IO features and their interactions play for satisfaction with international negotiation outcomes. Drawing on approaches of international negotiation and cooperation, hypotheses on individual, country and IO features are specified and examined empirically with a multilevel analysis. This reveals that especially individual and IO level features impact outcome satisfaction. Outcome satisfaction increases if delegates put in much work in negotiations and can conduct them flexibly and if IOs are small in size, and have institutional designs that seek to foster debates. The paper also shows that there are cross-level interaction effects. Most notably, the positive effect of flexibility on high outcome satisfaction is less pronounced when negotiations are more strongly characterized by bargaining dynamics. Vice-versa, when IOs are prone to arguing dynamics all actors become more satisfied.
Keywords: 320; International organizations; Multilateral negotiations; Survey; Comparative analysis; Outcome satisfaction; Theories of international negotiations and international cooperation; Individual-level characteristics; Country-level factors; IO-level factors; Multilevel analysis; Cross-level interactions